Women Worker Protection: A Systematic Review On Maternity Protection In Indonesia - Amriyati, Amriyati; Nurbaiti, Siti; Rumita, Masri; Layola Nainggolan, Fraya (Devotion : Journal of Research and Community Service, 2023)
Implementing maternity protection at the workplace is found significant benefits and cost savings to businesses, but many young women workers in garment factories in Indonesia remained vulnerable within their maternity period. This research was focused on why to have a clear and comprehensive overview on the need of women workers protection; how is women worker maternity protected. Through a Systematic Literature Review, data base was obtained through seven prominent publishers by writing key words “women worker protection and maternity protection”; inclusive articles were sorted by publication time 2012 – 2022; and the considerations of specific relevance of the article with this research questions. Other literature sources were also used to be added for more comprehensive literature review for the the research questions. It was found that breastfeeding was neglected by 33.6 million young working women in Indonesia, which costed US$1.5–9.4 billion annually, despite the prescription of the Constitution that worker shall have humane livelihood; fair treatment, and human dignity, in line with ILO and the SDG. Rights and measures on family leave, maternity leave, childcare and family services, social security and working conditions provisions will resulted in improved work performance, enhance female workers loyalty and reduce turnover. State shall more tightly supervise on the implementation of Law for protection of women worker rights and employer’s social solidarity, communality, and brotherhood